Characterization and partial purification of an antibacterial agent from halophilic actinomycetes Kocuria sp. strain rsk4 - Kumar, Ravi Ranjan (Tabriz University of Medical Sciences, 2018)

(untitled) (Bioimpacts)
[Image: see text] Introduction: The inevitable rise of antibiotic-resistant bacteria is a global health problem. These pathogens erode the utility of available antibiotics. Staphylococcus aureus is one of the major causes of community-acquired infections. The aim of work was to evaluate the marine actinomycetes for production of the antibacterial agent against pathogens. Methods: Halophilic actinomycetes were isolated, characterized and screened for production of antibacterial agent against pathogenic bacteria. The antibacterial compounds were extracted by solvent extraction and separated by TLC based bioautography. Antibacterial compound was further purified by flash chromatography followed by high-performance liquid chromatography (HPLC) techniques. The active fraction was characterized by spectroscopy techniques. The minimum inhibitory concentration of antibiotic was determined against pathogens. Results: A new halophilic actinomycetes strain rsk4 was isolated from marine water. It was designated as Kocuria sp. based on the physiological, biochemical and 16S rDNA sequencebased characters. It was able to produce broad-spectrum antibacterial compound and exhibited significant inhibitory activities against antibiotic-resistant S. aureus. The antibacterial compound was secreted optimally at 5% NaCl and neutral pH in the starch casein medium during stationary phase. The crude ethyl acetate extract was separated by chloroform-methanol, 24:1, v/v having Rf value 0.45. Bioassay of HPLC fractions confirms the presence of antibiotics picks at retention time: 3.24 minutes. The UV-Visible and mass spectra of the compound revealed that the active compound was different from other known antibiotics. The lowest minimum inhibitory concentration was recorded against S. aureus (30 µg/mL). Conclusion: The result suggests that a broad-spectrum antibacterial compound obtained from halophilic actinomycetes is effective against pathogenic bacteria. This compound may be a good alternative treatment against antibiotic-resistant pathogen S. aureus.